A performance comparison between a horizontal source and a vertical source heat pump systems for a greenhouse heating in the mild climate Elazig, Turkey - Benli, Huseyin (Pergamon-Elsevier Science Ltd, 2013)
The investigation presented in this article is aimed at demonstrating the technical and design feasibility of using ground-source heat pump systems in the mild climate applications for greenhouse heating, where heating requirements are dominant. An experimental comparison between a horizontal ground-source heat pump system and a vertical ground-source heat pump system was shown by focusing on the heating performance. For this purpose, an experimental set-up was constructed. The heating system mainly consists of two different ground heat exchangers, a heat pump, measuring units and a heating space of a model-sized glass greenhouse with 30 m(2) located in the greenhouse location. The heating coefficient of performances of the two ground-source heat pumps (COPHP,H-V) and the overall system (COPsys,H-V) were obtained to be in the range of 3.1-3.6 for HGSHP and 3.2-3.8 for VGSHP and 2.7-3.3 for HGSHP and 2.9-3.5 for VGSHP, respectively. Although significant savings are possible with these heating systems, a substantial investment in equipment and facilities may be required. The experimental results were obtained from November to April in heating seasons of 2007-2008. The results showed that the utilization of the ground-source heat pump is suitable for greenhouse heating in this district. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ground-source heat pump (GSHP); Greenhouse; Elazig; Renewable energy